strategi komunikasi pemerintah daerah dalam penataan kota pangandaran - erni setiawati (JURNAL PURNAMA BERAZAM, 2020)
This research is motivated by the arrangement of an area in Pangandaran Regency which includes tourism on the Pangandaran coast including the west coast an the east coast of pangandaran, discussing the communication strategies of the local government in structuring Pangandaran city, structuring the city is an important asset for the community and tourists in terms of development carried out by the Pangandaran Regerecy government claimed as a platform for Pangandaran Beach revitalization construction planning. With the revitalization construction or structuring pangandaran city, it is hoped that it can be a step in communication strategies that can become a world class tourism sector. The problem in this research it that many street vendors around Pangandaran the disorderly odong-odong businessmen are obstacles that occur in the pangandaran beach area. The purpose of this study is to find out the steps of the pangandaran disreict government communication strategy, as the informant or respondent in this study, namely the Regional Development Planning Agency and the Head of the Office of Public Spatial housing and residential areas. The theory that the researchers used in this study was the Theory of Communication Strategies, in this study the researchers used qualitative research using descriptive studies and study used data collection techniques namely interviews, observation, and documentation where the data obtained was relevant. From the results of research that has been done by researchers shows that the communication strategy of the local government in Pangandaran Beach planning with planning steps thay have been determined strating from th central and provincial communication, in this arrangement can achieve the desired target of many tourists who visit Pangandaran beach because Pangandaran beach in now is adequate facilities and street vendors are relocated to a more appropriate place.